PROSES HOTL DALAM MENGEKSPLORASI KONSEP DAN PROSES TENTANG PEMBUATAN KERAMIK - Miranda Nikki Mariana Tendean; Christophil Medellu; Jeane Tumangkeng (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This study describes the results of exploratory learning about local wisdom, namely making ceramics. The purpose of this study was to 1) find out the concepts and physics processes in the manufacture of ceramics 2) to know the learning process of higher order thinking in exploring the physics concepts in the ceramic making process. The main activity of this research is to explore the scientific concepts and processes of ceramic making, using the Type B Higher Order Thinking Learning in Democratic Interaction (HOTL-DI) model. This research begins with conducting observations at the ceramics-making training center in Pulutan Village. . The results of observations of data recording procedures for making ceramics are used as a reference for exploration of scientific concepts and processes. Exploration activities are carried out in 2 stages. The first stage is material exploration. The second stage was an exploration activity by a group of fifth grade physics education students. The results showed the learning process of higher order thinking through exploratory learning, where at the beginning of the exploration activity all students still experienced difficulties, but then their ability to explore objects developed.